2008
DOI: 10.1016/j.dci.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of pattern recognition receptors during the development of foetal sheep

Abstract: Pattern recognition receptors (PRRs) play a crucial role in the initiation of the adaptive immune response. Immunological competence of foetal lambs occurs progressively throughout gestation and in order to understand the role played by PRRs in foetal immunological competence we quantified transcript expression, in the skin and spleen, of the TLRs, key C-type lectins and CARD15 during the critical second trimester. These data show that lambs express the same spectrum of PRRs as the adult but that the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, they did not find statistical differences in the expression levels of TLR3 and TLR4 between 130 days gestation and newborn animals. The levels of TLRs in sheep skin and spleen have been reported previously (Nalubamba et al, 2008). Although newborn animals were not included in the study, it was reported that the levels of TLR7 and TLR8 in the spleen were significantly higher than that of pre-term lambs, and that the levels of TLR4 in the skin were higher than that of pre-term lambs (Nalubamba et al, 2008).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, they did not find statistical differences in the expression levels of TLR3 and TLR4 between 130 days gestation and newborn animals. The levels of TLRs in sheep skin and spleen have been reported previously (Nalubamba et al, 2008). Although newborn animals were not included in the study, it was reported that the levels of TLR7 and TLR8 in the spleen were significantly higher than that of pre-term lambs, and that the levels of TLR4 in the skin were higher than that of pre-term lambs (Nalubamba et al, 2008).…”
Section: Discussionsupporting
confidence: 60%
“…The levels of TLRs in sheep skin and spleen have been reported previously (Nalubamba et al, 2008). Although newborn animals were not included in the study, it was reported that the levels of TLR7 and TLR8 in the spleen were significantly higher than that of pre-term lambs, and that the levels of TLR4 in the skin were higher than that of pre-term lambs (Nalubamba et al, 2008). There were also no reported significant differences in TLR3 expression across age groups in the neonatal ovine skin or spleen.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We therefore identified genes that were stable early time points where the majority of the cells are mononucleic and forming small myotubes (culture days, 2-11) those stable in established myotubes (days [11][12][13][14][15][16][17][18][19][20] and those most stable for the entire culture period. When the raw Cq values obtained at each time point are compared ( Figure 3), it is clear that for the majority of the genes examined, stable expression is observed once myotubes have become established in the culture, whereas higher intra and intergroup variation is observed when myotubes are developing.…”
Section: Discussionmentioning
confidence: 99%
“…The least stable gene identified by all analysis methods was Sdha. Sdha has been used as a reference gene in a number of studies using different tissues [18,19], however its high inter and intragroup variation make it unsuitable for normalisation in salmon myogenic cell cultures.…”
Section: Discussionmentioning
confidence: 99%